Feed Retention of Silver Pompano (Trachinotus blochii) on Commercial Feeding with The Addition of Turmeric Extract (Curcuma domestica) - Kartini, Wiwi; Lumbessy, Salnida Yuniarti; Setyono, Bagus Dwi Hari (Aquaculture Department, University of Mataram, 2024)
Silver pompano is a high-value fish, yet the cost of commercial feed is a major challenge for fish farmers. This study explores the addition of turmeric extract to commercial feed as a potential strategy to improve feeding efficiency and reduce production costs. Conducted at the Lombok Marine Aquaculture Center, the 50-day experiment used a Completely Randomized Design (CRD) with four treatment levels (control, 10 ml, 15 ml, and 20 ml of turmeric extract per kg feed) and three replications, totaling 12 experimental units. Parameters measured included growth performance indicators like specific growth rate (SGR), feed conversion ratio (FCR), protein and fat retention, and water quality. Data was analyzed using ANOVA and Duncan tests to assess treatment effects. Results showed that turmeric extract significantly improved SGR, FCR, protein retention, and fat retention, although it had no significant impact on absolute weight, length, survival rate, or feeding efficiency. The optimal treatment was 20 ml/kg of turmeric extract, yielding an SGR of 4.92%, FCR of 2.48, protein retention of 18.64%, and fat retention of 22.37%, likely due to the presence of bioactive compounds such as flavonoids, alkaloids, tannins, terpenoids, and phenols.